BUDAYA LOKAL DALAM PERSPEKTIF DAKWAH: Studi Tentang Nilai-Nilai Dakwah Pada Budaya Pacu Jalur Kuantan Singingi, Riau - Saada, Siti (AT-TANZIR: JURNAL ILMIAH PRODI KOMUNIKASI PENYIARAN ISLAM, 2023)
Pacu Jalur is an annual event held in Kuantan Singing Regency, Riau. The spur culture has many cultural values ​​contained in it. One of the values ​​discussed in this paper is the da'wah values ​​contained in the spur culture. This research aims to reveal the da'wah values ​​that exist in the activities of Spur of the Lane. This research method is qualitative (looking for meaning from an understanding), and data collection techniques through Library Research studies, namely by collecting data by reading books, newspapers, television, and others that follow the research problem by taking a phenomenological approach. The results of this study are the da'wah values ​​contained in the spur culture: cooperation, hard work, patience, and optimism.